Binding of Dopamine D1 Receptor and Noradrenaline Transporter in Individuals with Autism Spectrum Disorder: A PET Study. (7th August 2020) - Kubota, Manabu; Fujino, Junya; Tei, Shisei; Takahata, Keisuke; Matsuoka, Kiwamu; Tagai, Kenji; Sano, Yasunori; Yamamoto, Yasuharu; Shimada, Hitoshi; Takado, Yuhei; Seki, Chie; Itahashi, Takashi; et al.
Abstract: Although previous studies have suggested the involvement of dopamine (DA) and noradrenaline (NA) neurotransmissions in the autism spectrum disorder (ASD) pathophysiology, few studies have examined these neurotransmissions in individuals with ASD in vivo. Here, we investigated DA D1 receptor (D1 R) and noradrenaline transporter (NAT) binding in adults with ASD ( n  = 18) and neurotypical controls ( n  = 20) by utilizing two different PET radioligands, [ 11 C]SCH23390 and ( S, S )-[ 18 F]FMeNER-D2, respectively. We found no significant group differences in DA D1 R (striatum, anterior cingulate cortex, and temporal cortex) or NAT (thalamus and pons) binding. However, in the ASD group, there were significant negative correlations between DA D1 R binding (striatum, anterior cingulate cortex and temporal cortex) and the "attention to detail" subscale score of the Autism Spectrum Quotient. Further, there was a significant positive correlation between DA D1 R binding (temporal cortex) and emotion perception ability assessed by the neurocognitive battery. Associations of NAT binding with empathic abilities and executive function were found in controls, but were absent in the ASD group. Although a lack of significant group differences in binding might be partly due to the heterogeneity of ASD, our results indicate that central DA and NA function might play certain roles in the clinical characteristics of ASD.